2012
DOI: 10.3998/ark.5550190.0013.819
|View full text |Cite
|
Sign up to set email alerts
|

6-Hydrazinonicotinic acid hydrazide: an useful precursor for chemo- and regioselective synthesis of new heteroaryl-linked pyridinohydrazones

Abstract: In order to demonstrate the reactivity differentiation between the two dinucleophilic centers in the 6-hydrazinonicotinic acid hydrazide hydrate (1), a series of seven new 6-[(2-(arylidene)hydrazinyl]nicotinohydrazides (4) was chemoselectively accessed from the reaction of 1 with seven aryl or heteroaryl aldehydes by a simple procedure in ethanol as solvent. In a subsequent study, cyclization reactions of 4 with some 4-alkoxy-1,1,1-trifluoroalk-3-en-2-ones or triethylorthoacetate were proceeded easily also in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…1,3,4-Oxadiazole derivative 187 was obtained with 64% yield from 6-(2-(4-chlorobenzylidene)hydrazino)nicotinic hydrazide by a [4 + 1] cyclocondensation reaction with triethylorthoacetate (Scheme 54). 133 Sureshbabu et al 134 reported the synthesis of S-linked 1,3,4oxadiazole-tethered N α -protected peptidomimetics under sonication using acid hydrazides as synthetic precurssor.…”
Section: Synthesis Of Five-membered Rings With Two Heteroatomsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,4-Oxadiazole derivative 187 was obtained with 64% yield from 6-(2-(4-chlorobenzylidene)hydrazino)nicotinic hydrazide by a [4 + 1] cyclocondensation reaction with triethylorthoacetate (Scheme 54). 133 Sureshbabu et al 134 reported the synthesis of S-linked 1,3,4oxadiazole-tethered N α -protected peptidomimetics under sonication using acid hydrazides as synthetic precurssor.…”
Section: Synthesis Of Five-membered Rings With Two Heteroatomsmentioning
confidence: 99%
“…1,3,4-Oxadiazole derivative 187 was obtained with 64% yield from 6-(2-(4-chlorobenzylidene)­hydrazino)­nicotinic hydrazide by a [4 + 1] cyclocondensation reaction with triethylorthoacetate (Scheme ) …”
Section: Reactions Of Acid Hydrazidesmentioning
confidence: 99%
“…In this transformation, the hydrazine and the hydrazide moieties exhibited similar reactivity, whereas in the presence of aldehyde as one other carbon donor moiety the hydrazine and the hydrazide groups were treated chemoselectively and regioselectivly. 225 …”
Section: Orthoester Reactions Under Solvent-free Conditionsmentioning
confidence: 99%